Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1080/13594320701307420
|View full text |Cite
|
Sign up to set email alerts
|

Psychological climate and individual factors as antecedents of work outcomes

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 46 publications
4
45
1
2
Order By: Relevance
“…We contend that reciprocation is a mechanism for followers to respond to the services they receive from their servant leaders and therefore that psychological climate affects OCB through the effect of reciprocation. Based on recent studies supporting a positive and significant effect of psychological climate on OCB (e.g., Carr, Schmidt, Ford, & DeShon, 2003;Parker et al, 2003;Schneider et al, 2005;D'Amato & Zijlstra, 2008;van Dierendonck, 2011), we propose Hypothesis 2 below. In addition, because we consider that servant leadership, job satisfaction, and psychological climate are individual determinants of OCB, we further argue that the three determinants taken together are positive and significant determinants of OCB (Hypothesis 3).…”
Section: Psychological Climate and Ocbmentioning
confidence: 97%
“…We contend that reciprocation is a mechanism for followers to respond to the services they receive from their servant leaders and therefore that psychological climate affects OCB through the effect of reciprocation. Based on recent studies supporting a positive and significant effect of psychological climate on OCB (e.g., Carr, Schmidt, Ford, & DeShon, 2003;Parker et al, 2003;Schneider et al, 2005;D'Amato & Zijlstra, 2008;van Dierendonck, 2011), we propose Hypothesis 2 below. In addition, because we consider that servant leadership, job satisfaction, and psychological climate are individual determinants of OCB, we further argue that the three determinants taken together are positive and significant determinants of OCB (Hypothesis 3).…”
Section: Psychological Climate and Ocbmentioning
confidence: 97%
“…Hechanova et al study to determine the relationship of empowerment with job satisfaction and performance in five different service sectors and pointed out psychological empowerment was positively correlated with both job satisfaction and performance [33]. Amato and Zijlstra specified organizational citizenship behavior as a mediator of the relationships between individual factors (psychological climate and self-efficacy) and work outcomes (quality of performance and emotional exhaustion) [34]. Yao and Wang showed that value internalization predicts higher job satisfaction and weaker turnover intentions via commitment [14].…”
Section: Employee Satisfaction Factors and Commitment To Organizationmentioning
confidence: 99%
“…budaya organisasi (Singh, et al, 1996), kepribadian (Mount & Barrick, 1998;Motowidlo, Borman, & Schmit, 1997), komitmen (Jaramilloa, Mulki, & Marshall, 2005;Al Ahmadi, 2009), kepuasan kerja (Judge, Bono, Thoresen, & Patton, 2001;Gu & Chi, 2009), pendidikan (Ng & Feldman, 2009), self-efficacy (Karatepea, Uludagb, Menevisc, Hadzimehmedagicc, & Baddarc, 2006;D'Amato & Zijlstra, 2008), pengalaman (Dokko, Wilk, & Rothbard 2008), stres kerja (Beehr & Newman, 1988;Luthans, 1998;Robbins, 2001;Kazmi, Amjad, & Khan 2008), sikap kerja (Riketta, 2008), ambiguitas peran (Knight, Kim, & Crutsinger, 2007), kecerdasan emosi (Chermiss, 1998;Boyatzis, 1999;Goleman, 2001), harga diri (Ferris, Lian, Brown, Pang, & Keeping, 2010).…”
Section: Pendahuluanmentioning
confidence: 99%